Magnetic ionic liquid/polymer composites: Tailoring physico-chemical properties by ionic liquid content and solvent evaporation temperature. (1st December 2019) - Correia, D.M.; Fernandes, L.C.; García-Astrain, C.; Tariq, M.; Esperança, J.M.S.S.; de Zea Bermudez, V.; Lanceros-Méndez, S.
Abstract: This works reports on the development of magnetic composites based on the magnetic ionic liquid (MIL) 1-butyl-3-methylimidazolium tetrachloroferrate, ([Bmim][FeCl4 ]) and the electroactive polymer poly(vinylidene fluoride-trifluorethylene) (P(VDF-TrFE)). The composites were obtained at different solvent evaporation temperatures (≈25, 90 and 210 °C) and with different MIL contents (10, 20 and 40 wt%). It was concluded that the composites morphology is dependent on the evaporation temperature, allowing to obtain porous membranes with interconnected pores. A decrease in the crystallinity degree resulted upon increasing MIL content. The stability of P(VDF-TrFE) is slightly affected by the inclusion of MIL and by the solvent evaporation temperature used during the processing of the composites. The composites exhibit paramagnetic behavior. Tailoring of the magnetic susceptibility was possible through the control of the MIL content and solvent evaporation temperature. Graphical abstract: Image 1 Highlights: P(VDF-TrFE)/[Bmim][FeCl4 ] composite films were prepared by solvent casting. Solvent evaporation temperatures and [Bmim][FeCl4 ] contents were varied in sample preparation. The morphology of the samples can be tune4d by varying solvent evaporation temperature. The physico-chemical properties of the samples mainly depend on IL content.